NATURALISM. Issue 56 (2020) - Oppy, Graham
Abstract : I offer a minimal characterization of naturalism, with ontological, epistemological, psychological and evaluative dimensions. I explain why naturalism is attractive. I note that naturalists disagree among themselves about, among other things, the nature of values, beliefs, and abstractions. I close by responding to some standard objections to naturalism.